Beijing lectures on the grade restriction rule - Eager, Richard; Hori, Kentaro; Knapp, Johanna; Romo, Mauricio (Chinese annals of mathematics, 2017)
The authors describe the relationships between categories of B-branes in different phases of the non-Abelian gauged linear sigma model. The relationship is described explicitly for the model proposed by Hori and Tong with non-Abelian gauge group that connects two non-birational Calabi-Yau varieties studied by Rødland. A grade restriction rule for this model is derived using the hemisphere partition function and it is used to map B-type D-branes between the two Calabi-Yau varieties.